Real-World Evidence for Comparative Outcomes between Innovator and Biosimilar Bevacizumab in Advanced Colorectal Cancers - Vaidyanathan, Arvind; Vana, Pranaya; Joshi, Nachiket; Sourav, Bikash; Bhargava, Prabhat; John, George; Ramaswamy, Anant; Ostwal, Vikas (South Asian Journal of Cancer, 2024)
Generic versions of bevacizumab are commonly used in India in patients with advanced/metastatic colorectal cancers (mCRCs), but there is limited real-world evidence (RWE) about their efficacy in comparison to the innovator bevacizumab.Patients diagnosed with mCRC between January 2017 and January 2022 and receiving a combination of chemotherapy and bevacizumab were retrospectively analyzed for demographic variables and survivals. The primary endpoint of the study was the estimation and comparison of median progression-free survival (mPFS) between patients receiving innovator versus generic bevacizumab as first-line therapy (CT1) by the Kaplan–Meier method.A total of 944 patients were included in the analysis, of whom 652 patients (69%) received bevacizumab as CT1, 449 patients (48%) during second-line chemotherapy (CT2), and 74 patients (8%) during third-line therapy (CT3). The innovator was administered to 132 patients (14%), while the remaining 812 patients (86%) received a generic molecule. With a median follow-up of 18 months, there was no difference in mPFS between patients receiving the innovator or biosimilar (10 vs. 9.3 months, p = 0.62). Similarly, there was no difference in median overall survival (mOS) between patients receiving the innovator or biosimilar during CT1 (17.8 vs. 18 months, p = 0.85). Among the patients who received bevacizumab during CT2, there was no statistically significant difference in mPFS between the innovator and the biosimilar (5.5 vs. 5.8 months, p = 0.97), nor was there a difference in mOS between patients receiving the innovator or biosimilar during CT2 (8.15 vs. 8.58 months, p = 0.16).The current study offers RWE to suggest similar outcomes with innovator and generic bevacizumab when combined with chemotherapy in mCRCs. This has significant implications in India and other low- and middle-income countries besides providing oncologists with greater confidence to use these molecules in their clinical practice.
Keywords: colorectal cancer; bevacizumab; biosimilar; LMICS; Real-world evidence